Pharmacological Manipulation of Peripheral Vascular Resistance in Single Ventricle Patients (Stages I, II, and III of Palliation) - M. Schwartz, Steven; A. Floh, Alejandro; C. Laussen, Peter (Current Vascular Pharmacology, 2016)
Pharmacological manipulation of afterload is often used in the management of single ventricle patients, both in the acute post-operative setting and more chronically. After the first stage of palliation the pulmonary and systemic circulations are in parallel and afterload reduction is often used to increase total cardiac output and systemic oxygen delivery. The effectiveness of this approach is likely to be dependent on the intrinsic contractile state of the myocardium as well as the post-operative vascular tone. A variety of clinical studies and theoretical models support this approach. The use of afterload reduction in this context must be balanced with the need to maintain a critical systemic blood pressure for organ perfusion and to promote pulmonary blood flow. After the second and third stages of palliation the use of acute afterload reduction is less complex and primarily directed at promoting cardiac output when it is low and/or controlling high blood pressure. Second stage palliation is particularly unique in that the cerebral and pulmonary circulations are in series and respond differently to many manipulations designed to control vascular resistance. The incidence of long-term circulatory failure in single ventricle patients has led to frequent use of afterload reducing agents in this population but data to suggest that this improves overall outcomes is lacking. Newer studies suggest there may be a role for drugs that reduce pulmonary vascular resistance. This chapter will discuss the principles of manipulation of systemic vascular resistance, or afterload, following each of the three stages of single ventricle reconstruction. This article addresses the seventh of eight topics comprising the special issue entitled “Pharmacologic strategies with afterload reduction in low cardiac output syndrome after pediatric cardiac surgery”.
Keywords: postoperative management